CMET-18. IMPACT OF KRAS MUTATION STATUS ON THE EFFICACY OF IMMUNOTHERAPY IN LUNG CANCER BRAIN METASTASES - Lauko, Adam (Neuro Oncol, 2019)
BACKGROUND: Immunotherapy is increasingly used in patients with non-small cell lung cancer brain metastases (NSCLCBM). KRAS mutations are associated with worse prognosis and there is no FDA approved targeted therapy. KRAS mutations are associated with increased expression of PD-L1. We evaluated the outcomes of NSCLCBM with KRAS mutations treated with immune checkpoint inhibitors (ICI). METHODS: We reviewed 800 patients with NSCLCBM treated at our tertiary care center. 226 had known KRAS mutational status, 121 of which received immunotherapy. Overall survival (OS) was calculated from either the start of immunotherapy (when both groups received immunotherapy) or from the date of diagnosis of brain metastasis. Kaplan-Meier method and Cox Proportional hazard model were utilized to determine differences in OS and the Chi-square test was utilized to determine differences in PD-L1 expression. RESULTS: In 109 patients where both KRAS and PD-L1 status were known, KRAS mutations had greater PD-L1 expression (80.1% vs 61.9% positive, p=0.04). There was no difference in OS between KRAS mutant vs KRAS wild-type patients treated with immunotherapy. Median survival from the start of immunotherapy was 15.6 vs 15.5 months respectively (p=0.7), after adjusting for age, KPS, lesion number and extra-cranial metastasis (HR = .91, p=.7). Patients with KRAS mutations treated with immunotherapy versus those who received chemotherapy had a 1-year OS from the diagnosis of brain metastasis of 60.9% vs 38.7% respectively (trending towards significance, p=0.05). KRAS wild-type patients treated with immunotherapy versus those who did not receive immunotherapy had a 1-year OS from the diagnosis of brain metastasis of 61.9% vs 62.5% (p=0.85), respectively. DISCUSSION: KRAS mutations are associated with increased PD-L1 expression. Use of immunotherapy negates the poor outcomes seen traditionally in patients with NSCLCBM and KRAS mutations and it improves survival compared to use of chemotherapy. Our experience supports the use of immunotherapy in these patients.